(untitled) (Revista Científica Ciencias Naturales y Ambientales, 2015)
The ability of Dunaliella to increase the lipid content under stress conditions imposed by physical or chemical stimuli, makes it one of the most studied genera for lipid production. The aim of this study was establish the influence of different concentrations of sodium chloride (0,1 M and 2 M) and nitrogen (2 mM and 20 mM) in relation to a control medium (0,5 M NaCl and 10 mM NO3 -) in the production of total lipids from a native strain of Dunaliella sp. The highest cellular density was obtained with the salinity 0,5 M (2,7 ± 0,15 x107 cel/mL) and the nitrogen concentration 20 mM (3,29 ± 0,21 x 107 cel/mL). The high lipid per gram of biomass (13,99%) and liter of culture (7,83%) among salinity treatments were obtained with the molarity 2 M NaCl. Among nitrogen treatments, the highest lipids per gram of biomass (16,88%) and per liter of culture (8,10%) were reached in 20 mM NO3 -. The obtained results suggest that the high salinities and nitrogen concentrations influence the lipid production of Dunaliella sp.